The role of the gut microbiome in the intergenerational transmission of the obesity phenotype: A narrative review - Tang, Mabel; Marroquin, Elisa (Frontiers in Medicine, 2022)
Obesity is considered an epidemic by the World Health Organization. In particular, maternal obesity can affect the development of obesity and other related metabolic disorders in infants. Recently, both animal and human studies have pointed to the importance of the gut microbiome in facilitating the transmission of the obesity phenotype from mother to offspring. The gut microbiome changes significantly during the progression of pregnancy, and the microbiota of the amniotic fluid and placenta have recently been shown to colonize the infant gut in utero. Microbial composition, diversity, and richness are significantly altered by maternal obesity, which in turn affects the infant’s acquisition of the gut microbiome and their risk to develop metabolic disorders. C-section has also been shown to affect the colonization of the infant gut and offspring metabolic and immune health. This narrative review seeks to discuss the role of the gut microbiome in the transmission of the obesity phenotype from mother to child, as well as how birth delivery, breastfeeding, and probiotic interventions may modulate this relationship.